Comparison of maximal heart rate obtained in three different situations. (Fiep Bulletin - online, 2015)
Compare Futsal players' HRmax obtained in three different situations: competition (HR1), 220age equation (HR2), and maximal incremental test (HR3). Methods: Ten female athletes (161.0  3.8 cm height; 17.20  19.5 years; 23.7  4.4% body fat; 40.0  3.8 mLO2.kg-1.min-1 VO2max) belonging to a futsal team from Belo Horizonte that had won the 2002 Metropolitan Championship were evaluated. To measure HRmax during the matches and during the maximal incremental test, the volunteers used a Polar Vantage® heart rate monitor. HR1 was taken as the highest HR of each player during matches. HR2 was estimated using the following equation: HRmax = (220  age). HR3 was determined as the highest HR recorded during a maximal incremental test until fatigue performed on a bicycle ergometer. Wilcoxon Rank Sum and Pearson Chi-Square tests were used in statistical analysis with significance level of p
Keywords: Maximal Heart Rate; Intensity; Futsal.